Library ethics - Preer, Jean L. (Westport, Conn. : Libraries Unlimited, 2008)
This book includes historical precedents and current examples of ethical issues facing the profession. It looks broadly at the many arenas in which librarians face ethical choices, helping practitioners identify an ethical dilema and providing guidacne on how to respond , how to separate personal belief from professional responsibility, and how to make exceptions in a principled way.
Includes bibliographical references (p. [239]-245) and index.
osc 02/05/13
Loans
Keywords: Librarians -- Professional ethics; Library science -- Moral and ethical aspects